Elevated Temperature, Freezing-Thawing and Mechanical Properties of Limestone, Marble, and Basalt Powders Reinforced Metakaolin-Red Mud-Based Geopolymer Mortars - Chakkor, Ouiame; Altan, Mehmet Fatih; Canpolat, Orhan (SPRINGER INT PUBL AG, 2022)
In this work, metakaolin and red mud-based geopolymer specimens were produced with three categories of different filler materials (limestone powder, marble powder, and basalt powder), replaced with river sand of different ratios 25, 50, and 75%. The mixture is activated with an activator that consists of sodium silicate (Na2SiO3) and sodium hydroxide (NaOH). The manufactured samples were exposed to 180 cycles of freezing-thawing and high-temperature effects at 200, 400, 600, and 800 degrees C. Furthermore, compressive and flexural strengths at 7, 28, and 56 days, ultrasonic pulse velocity, void ratio, and splitting-tensile tests were performed. Moreover, SEM analyses were conducted to examine the microstructure properties and a visual inspection. It has been observed that basalt powder series after exposure to high temperatures yielded higher strength properties than limestone and marble powder samples. For the freezing-thawing effect, the basalt powder series sustained higher results for compressive strength. In contrast, regarding flexural strength results, the limestone powder series improved its competence in terms of 180 cycles. Experimental test results indicated that the use of filler materials on metakaolin and red mud geopolymer enhanced positively on compressive and flexural strength properties with 75.63 and 14.24 MPa, respectively, for basalt powder samples. Additionally, the uses of different filler materials significantly impact the void ratio, water absorption, and splitting tensile.
Keywords: Geopolymer; Binder; Metakaolin; Red mud; Filler materials; Durability; FLY-ASH; SILICA FUME; THERMAL-BEHAVIOR; PERFORMANCE; STRENGTH; CONCRETE; CEMENT; WASTE; MICROSTRUCTURE; EXPOSURE; Engineering